Whole-Body Metabolism, Carbohydrate Utilization, and Caloric Energy Balance After Sport Concussion: A Pilot Study. (July 2020) - Walton, Samuel R.; Malin, Steven K.; Kranz, Sibylle; Broshek, Donna K.; Hertel, Jay; Resch, Jacob E.
Background: Sport concussion (SC) causes an energy crisis in the brain by increasing energy demand, decreasing energy supply, and altering metabolic resources. Whole-body resting metabolic rate (RMR) is elevated after more severe brain injuries, but RMR changes are unknown after SC. The purpose of this study was to longitudinally examine energy-related changes in collegiate athletes after SC. Hypothesis: RMR and energy consumption will increase acutely after SC and will return to control levels with recovery. Study Design: Case-control study. Level of Evidence: Level 4. Methods: A total of 20 collegiate athletes with SC (mean age, 19.3 ± 1.08 years; mean height, 1.77 ± 0.11 m; mean weight, 79.6 ± 23.37 kg; 55% female) were compared with 20 matched controls (mean age, 20.8 ± 2.17 years; mean height, 1.77 ± 0.10 m; mean weight, 81.9 ± 23.45 kg; 55% female). RMR, percentage carbohydrate use (%CHO), and energy balance (EBal; ratio between caloric consumption and expenditure) were assessed 3 times: T1, ≤72 hours after SC; T2, 7 days after T1 ; and TF, after symptom resolution. A 2 × 2 × 3 (group × sex × time) multivariate analysis of variance assessed RMR, %CHO, and EBal. Changes in RMR, %CHO, and EBal (T1 to TF ) were correlated with days to symptom-free and days to return to play in the concussed group. Results: Women reported being symptom-free (median, 6 days; range, 3-10 days) sooner than men (median, 11 days; range, 7-16 days). RMR and %CHO did not differ across time between groups or for group × sex interaction. SC participants had higher EBal than controls at T1 ( P = 0.016) and T2 ( P = 0.010). In men with SC, increasing %CHO over time correlated with days to symptom-free ( r = 0.735 and P = 0.038, respectively) and days to return to play ( r = 0.829 and P = 0.021, respectively). Conclusion: Participants with SC were in energy surplus acutely after injury. Although women recovered more quickly than men, men had carbohydrate metabolism changes that correlated with recovery time. Clinical Relevance: This pilot study shows that male and female student-athletes may have differing physiologic responses to SC and that there may be a role for dietary intervention to improve clinical outcomes after SC.